Determining the Spoilage Threshold for Ground Beef Using Multiple Objective Measures - Lauren M. Frink; Stephanie L. Witberler; Mason J. Prester; Erin S. Beyer; Jessie L. Vipham; Morgan D. Zumbaugh; Michael D. Chao; Travis G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2025)
Objective: The objective of this study was to determine the point at which ground beef reaches spoilage as determined by consumers. Study Description: Retail ground beef packages were procured from a ground beef facility and randomly assigned to a storage duration (0 – 14 days) for simulated retail display. Packages were stored in mother bags at 36 to 40°F in the absence of light until placed in the retail case under fluorescent lights on the designated display date. Samples were displayed in three coffin-style cases at 36 – 40°F for eight different display periods (0, 2, 4, 6, 8, 10, 12, and 14 days). Consumer sensory panelists evaluated eight samples for visual appearance, odor, and touch. For each measure, consumers were asked if they would purchase the sample and if they considered the sample spoiled. Trained sensory panelists evaluated the same samples on the same day of display and were asked to evaluate redness, percent discoloration, odor, and touch characteristics. Results: Consumers were less (P < 0.05) likely to purchase and more (P < 0.05) likely to rate samples spoiled once samples reached 8 days of display for visual appearance, touch, and odor. Consumer evaluation of the visual appearance score of the samples showed the strongest relationship to spoilage, having a high R2 of 0.89 (P < 0.05). Threshold values of 50%, 75%, 90%, and 95% were identified for consumer purchase intent likelihood using multiple objective measures. With an R2 of 0.86 (P < 0.05), trained panel redness scores of 60.15, 73.9, 87.6, and 96.95 corresponded to 50%, 75%, 90%, and 95% likelihood of a consumer purchasing the product. The likelihood of consumers classifying a sample as spoiled (R2 = 0.76) 5%, 10%, 25%, and 50% of the time corresponded with a trained sensory panel redness score of 74.8, 64.1, 48.4, and 32.7, respectively. Overall, consumers’ opinion toward the product’s appearance plays the biggest role in their purchase intent and assessment of spoilage as opposed to touch and odor. The Bottom Line: Though many changes were identified throughout the retail display period, the change in color from a bright, cherry-red to brown was shown to be the most important factor considered by consumers when they identified whether or not samples were spoiled; therefore, maintaining beef in a bright, cherry-red state is crucial to maximizing value.
Keywords: ground beef; spoilage; consumer